Crenças envolvendo o não aprender: um estudo evolutivo sobre a construção do conhecimento social - Saravali, Eliane Giachetto [UNESP]; Guimarães, Taislene [UNESP]; Guimarães, Karina Perez; Melchiori, Ana Paula [UNESP] (Universidade Federal de Minas Gerais (UFMG), Faculdade de Educação, 2013)
The construction of social knowledge, under the Piagetian approach, has been the target of recent research in the Brazilian context. From this perspective, this article presents preliminary data from an evolutionary study regarding the ideas of children and adolescents about not learning. Herein we present data obtained from the second methodological tool used in this research: an analysis of a story involving a situation of not learning, applied to 80 students between 06 and 16 years old. The main results indicate that most of the students surveyed tend to blame only themselves for not learning. They justify it by factors such as indifference, indiscipline, among others. Students' beliefs are also analyzed according to levels of understanding of social reality and most students presented a very elementary level of understanding.

A construção do conhecimento social, sob o enfoque piagetiano, vem sendo alvo de pesquisas recentes no contexto brasileiro. Nessa perspectiva, o presente artigo traz dados parciais de um estudo evolutivo a respeito das ideias de crianças e adolescentes sobre a não aprendizagem. Apresentamos aqui os dados obtidos a partir do segundo instrumento metodológico utilizado na pesquisa: a análise de uma história envolvendo uma situação de não aprendizagem, aplicada em 80 escolares entre 6 e 16 anos. Os principais resultados indicam que a maioria dos sujeitos tende a responsabilizar somente os alunos pela não aprendizagem, justificando-a por meio de fatores como desinteresse, indisciplina, entre outros. As crenças dos sujeitos são analisadas também conforme os níveis de compreensão da realidade social e se apresentam, para a maioria deles, no nível mais elementar.
Beliefs involving not learning: an evolutionary study on the social construction of knowledge
Keywords: Conhecimento Social; Estudo Evolutivo; Aprendizagem; Social Knowledge; Evolutionary Study; Learning